TO XX RUSSIA SURGICAL OLYMPIAD: RESULTS AND PERSPERCTIVE - S. S. Dydykin; B. V. Kozlovskii (Сеченовский вестник, 2022)
Results and perspectives of Surgical Olympiad as one of the clue elements of basic education of surgeons are discussed